2015
DOI: 10.1002/prp2.173
|View full text |Cite
|
Sign up to set email alerts
|

Interrogating the relationship between rat in vivo tissue distribution and drug property data for >200 structurally unrelated molecules

Abstract: The ability to explain distribution patterns from drug physicochemical properties and binding characteristics has been explored for more than 200 compounds by interrogating data from quantitative whole body autoradiography studies (QWBA). These in vivo outcomes have been compared to in silico and in vitro drug property data to determine the most influential properties governing drug distribution. Consistent with current knowledge, in vivo distribution was most influenced by ionization state and lipophilicity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Nonspecific binding (NSB) strongly influences the quality of imaging agents, as well as the pharmacological properties of drug candidates . The identification of such molecules often requires extensive optimization efforts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonspecific binding (NSB) strongly influences the quality of imaging agents, as well as the pharmacological properties of drug candidates . The identification of such molecules often requires extensive optimization efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Nonspecific binding (NSB) strongly influences the quality of imaging agents, [1,2] as well as the pharmacological properties of drug candidates. [3] The identification of such molecules often requires extensive optimization efforts. After am edicinal chemistry program hasadvanced beyond acertain stage, it becomes very challenging to significantly improvet he physicochemicalp roperties of advanced candidates without losing desirable pharmacological properties.…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to improvement in lipophilicity (log P) of 5‐HMT by substitution of sulphur atoms (Figures , ). It was reported that lipophilicity of a small molecule will influence membrane partitioning and cell permeability . Furthermore, Fontana‐Masson staining was used to spot melanocytes in the epidermis of the UV‐exposed dorsal skin and confirmed that melanocyte spots were decreased in 5‐HMT‐treated mice (Figure C).…”
Section: Resultsmentioning
confidence: 55%
“…It was reported that lipophilicity of a small molecule will influence membrane partitioning and cell permeability. [10] Furthermore, Fontana-Masson staining was used to spot melanocytes in the epidermis of the UV-exposed dorsal skin and confirmed that melanocyte spots were decreased in 5-HMT-treated mice ( Figure 2C). As a confirmatory measure of UV-induced melanogenesis and depigmentation effects of 5-HMT, immunohistochemistry staining using S100 protein, widely-used melanocyte marker protein, was performed.…”
Section: Anti-melanogenic Effects Of 5-hmt On Uvb-induced Skin Pigmenmentioning
confidence: 58%
“…The HIE reaction has become a broadly utilized and elegant method for the incorporation of deuterium or tritium into organic molecules, circumventing the need for a tedious multi-step synthesis. [2] In drug discovery, radioactive tritium substances are used as research tools [3,4] for example, for understanding tissue distribution, [5] in covalent binding assays, [6] or for ADME (absorption distribution metabolism excretion) profiling of new drug candidates. [7] Numerous HIE protocols utilizing homogeneous or heterogeneous catalysts have already been described.…”
mentioning
confidence: 99%